2012
DOI: 10.1111/j.1747-6593.2012.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient release from integrated constructed wetlands sediment receiving farmyard run‐off and domestic wastewater

Abstract: Constructed wetland sediments are frequently contaminated with nitrogen and phosphorus. There is a risk that accumulated pollutants can either be remobilised or reach the groundwater. Five identical mesocosms, which were filled with subsoil collected from full‐scale integrated constructed wetland (the first cell receives the most contaminated influent), were set up to examine nutrient removal within sediment layers. The results indicated that accumulated nutrients leached out into inflow water and that the sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
(56 reference statements)
1
4
0
Order By: Relevance
“…L. minor and A. filiculoides are plants with small roots and the rapid growth of these plants was controlled by frequent harvesting. The nitrification and denitrification rates were found to be similar to studies by Kyambadde et al (2004a, b), Ozturk et al (2005), Ozengin and Elmaci (2007), Patel and Kanungo (2010) and Dong et al (2013) that worked on the FTWs. This resulted in these FTWs having the upper part of water zone being aerobically conditioned, while the lower part was anaerobic.…”
Section: Potential Nitrification and Denitrificationsupporting
confidence: 73%
See 2 more Smart Citations
“…L. minor and A. filiculoides are plants with small roots and the rapid growth of these plants was controlled by frequent harvesting. The nitrification and denitrification rates were found to be similar to studies by Kyambadde et al (2004a, b), Ozturk et al (2005), Ozengin and Elmaci (2007), Patel and Kanungo (2010) and Dong et al (2013) that worked on the FTWs. This resulted in these FTWs having the upper part of water zone being aerobically conditioned, while the lower part was anaerobic.…”
Section: Potential Nitrification and Denitrificationsupporting
confidence: 73%
“…Ghobrial and Siam 1998;Ash and Truong 2003;Todd et al 2003), acid mine drainage treatment (e.g. Smith and Kalin 2000), piggery effluent treatment (e.g., Ash and Truong 2003;Hubbard et al 2004), poultry processing wastewater treatment (e.g., Todd et al 2003), and water supply (e.g., Garbett 2005;Dong et al 2013). FTWs have proved to be effective in removing suspended solids, nutrients, and heavy metals like copper, zinc, and cadmium (Headley et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might have been due to the contribution of the DOC originating from the decaying plant material accumulating in the sediment, as reflected by the high organic matter content of the sediment. [68], studying the nutrient release from integrated constructed wetland sediments, also found that sediments released substantially more organic matter than the incoming organic matter that could be degraded. The living reed roots and rhizomes are also capable of emitting DOC to a greater degree during the active growth period [69].…”
Section: P Australismentioning
confidence: 99%
“…The most common way to recover phosphorus from sludge is landspreading of sludge as fertilizer in agricultural applications. However, this method has been limited in some countries of Europe because of heavy metals, pathogens and toxic organic contents in the sludge and the questionable bioavailability of the metal phosphates bound in the sludge (Dong et al, 2013;Semerci, Ahadi, & Cos ¸gun, 2021;Vardanyan et al, 2018). Therefore, wet chemical or thermal treatment processes have been utilized to recover phosphorus from the MDS in recent years (Gorazda et al, 2017, Law & Pagilla, 2018.…”
mentioning
confidence: 99%